Study of Congo Red Adsorption by Chitosan-Graphene Oxide (Chitosan-GO) Composite Synthesize with Hydrothermal Synthetic Method: Optimization and Determination Condition - Desnelli Desnelli; Siska Safitri; Eva Musifa; Afreni Hamidah; Suheryanto Suheryanto; Ady Mara; Muhammad Said (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
This research aims to synthesize chitosan-graphene oxide (chitosan-GO) material using the hydrothermal method at varying material ratios and adsorption studies on Congo red. Chitosan-GO composites were synthesized with mass ratios of (1:1), (1:3) and (1:5). The synthesized chitosan-GO composite was applied to absorb Congo red dye. The adsorption process is carried out by varying pH, contact time, concentration and temperature. The chitosan-GO composite was characterized using XRD, BET and SEM-EDS. The results of XRD characterization of the chitosan-GO composite with a ratio of 1:1 showed a diffractogram of 2θ = 22.3°, at a ratio of 1:3 the diffractogram angle was 2θ = 22.1°, while the ratio (1:5) of the diffractogram peak obtained was 2θ = 22.8°. The surface area obtained in chitosan-GO composite was 11.60 m2/g. The morphology of the chitosan-GO composite (1:5) is in the form of crystalline lumps with the constituent elements C (65.98%), O (32.68%), Na (0.22%) and S (0.09%). Adsorption of Congo red dye using chitosan-GO composite obtained optimum conditions at pH 7, contact time 50 minutes, Congo red concentration 45 mg/L and temperature 50°C. The adsorption isotherm is in accordance with the Langmuir isotherm model and the maximum adsorption capacity (Qm) is 10.245 mg/g.